Soft Power and Stress: The Health Impacts of Indonesian Soap Operas on Malaysian Millennials - Rangga Cipta Perdana; Ernida Kadir; Genta Iverstika Gempita (GHMJ (Global Health Management Journal))
Background: The onslaught of Indonesian popular culture in Malaysia is an inevitable phenomenon. It enters without being prevented because of its presence in addition to the factor of technological sophistication, also because of the demand of many Malaysian audiences. The number of soap operas has infuriated certain circles. The reason is that the Indonesian culture that is born in Indonesian soap operas is shredded and superstition and it is not in accordance with the culture in Malaysia. All of this raises concerns that the presence of Indonesian culture will affect the identity, religion, and language, of the local community.